1980
DOI: 10.1177/001316448004000143
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Selected Personality Traits and Self-Esteem Among Female Nursing Students

Abstract: For a sample of 75 female senior nursing students, responses to the need scales of the Adjective Check List (ACL) were correlated with Total P Scores from the Tennessee Self-Concept Scale. The measure of self-esteem exhibited statistically significant correlation coefficients of .30 ( p < .02), .39 ( p < .01), and .34 ( p < .01) with the ACL scales of Endurance, Nurturance, and Affiliation. Statistically significant negative coefficients of -.31 ( p < .01), and -.51 ( p < .01) were found for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Positive correlation with nursing student self-esteem Negative correlation with nursing student self-esteem Relational abilities: assertiveness [41,78], ability to communicate [56] Mental health indicators: despair or depression [47,59,64,84,85,87,88], mental illness [87,89], stress [43,58,70,82], state anxiety [43,53,59,63] Feeling management: emotional intelligence [78], effective coping [57,70,[79][80][81][82] and effective feeling management strategies [83], anger management [64,68] Relational characteristics: negative relationships [89], aggressive behaviours [90] Self-evaluation: self-perception, ability to self-assess, self-efficacy [40] Personal characteristics: youth [46], female gender [46,50] Personal characteristics: religious beliefs [84,85], familial cohesion, social and emotional support [80,82,83], health status in general [82] or good mental health [63,81] Attrition, via self...…”
Section: Mruk's Two-dimensional Conception Of Self-esteemmentioning
confidence: 99%
“…Positive correlation with nursing student self-esteem Negative correlation with nursing student self-esteem Relational abilities: assertiveness [41,78], ability to communicate [56] Mental health indicators: despair or depression [47,59,64,84,85,87,88], mental illness [87,89], stress [43,58,70,82], state anxiety [43,53,59,63] Feeling management: emotional intelligence [78], effective coping [57,70,[79][80][81][82] and effective feeling management strategies [83], anger management [64,68] Relational characteristics: negative relationships [89], aggressive behaviours [90] Self-evaluation: self-perception, ability to self-assess, self-efficacy [40] Personal characteristics: youth [46], female gender [46,50] Personal characteristics: religious beliefs [84,85], familial cohesion, social and emotional support [80,82,83], health status in general [82] or good mental health [63,81] Attrition, via self...…”
Section: Mruk's Two-dimensional Conception Of Self-esteemmentioning
confidence: 99%
“…An interesting measure of self-esteem designed for mature populations is the Self-esteem Index developed by Barksdale (Barksdale, 1972;Dagenais, 1977;Moran, Michael, & Dembo, 1978). A recent study of self-esteem and personality traits among nursing students has been reported by Lewis, Bentley, & Sawyer (1980). For this study the Barksdale Self-esteem Index was correlated with the 14 primary Omnibus Personality Inventory scales and the secondarily derived Intellectual Disposition Category scale of the Inventory.…”
mentioning
confidence: 94%